Knowledge, Attitude, Awareness, and Barriers Toward Influenza Vaccination Among Medical Doctors at Tertiary Care Health Settings in Peshawar, Pakistan-A Cross-Sectional Study - Iftikhar Ali; Iftikhar Ali; Iftikhar Ali; Muhammad Ijaz; Inayat U. Rehman; Inayat U. Rehman; Afaq Rahim; Humera Ata (Frontiers Media S.A., 2018)
Objective: This study intends to evaluate the knowledge, attitude and awareness of medical doctors toward influenza vaccination and the reasons for not getting vaccinated.Methods: A cross-sectional study was carried out among medical doctors in three major tertiary care health settings in Peshawar, Khyber Pakhtunkhwa (KP), Pakistan. A web-based, pre-tested questionnaire was used for data collection.Results: A total of (n = 300) medical doctors were invited, however only (n = 215) participated in the study with a response rate of 71.7%. Among the participants, 95.3% (n = 205) were males with a mean age of 28.67 ± 3.89 years. By designation, 121(56.3%) were trainee medical officers and 40 (18.6%) were house officers. The majority 102(47.4%) had a job experience of 1-2 years. Of the total sample, 38 (17.7%) doctors reported having received some kind of vaccination, whereas only 19 (8.84%) were vaccinated against influenza. The results identified that the major barriers toward influenza vaccinations included (1) Unfamiliarity with Influenza vaccination availability (Relative Importance Index RII = 0.830), (2) Unavailability of Influenza vaccines due to lack of proper storage area in the institution (RII = 0.634), (3) Cost of vaccine (RII = 0.608), and (4) insufficient staff to administer vaccine (RII = 0.589). Additionally, 156 (72.6%) of doctors were not aware of the influenza immunization recommendation and guidelines published by the Advisory Committee on Immunization Practices (ACIP) and Centre for Disease Control and Prevention (CDC). Physicians obtained a high score (8.27 ± 1.61) of knowledge and understanding regarding influenza and its vaccination followed by medical officers (8.06 ± 1.37). Linear Regression analysis revealed that gender was significantly associated with the knowledge score with males having a higher score (8.0± 1.39) than females (6.80 ± 1.61 β = −1.254 and CI [−2.152 to −0.355], p = 0.006).Conclusion: A very low proportion of doctors were vaccinated against influenza, despite the published guidelines and recommendations. Strategies that address multiple aspects like increasing awareness and the importance of the influenza vaccine, the international recommendations and enhancing access and availability of the vaccine are needed to improve its coverage and health outcomes.